(3TQM GdCUhd GdNeSIs - (3CHh GdMSf Hf YHO GdLHGQs
(3ChdgG (B:s
(3hHYO aEfeG ChQOg ai GdZeO ajg daX GdEYJbGO hGdYde HGdCKfjf YeG djS HYde s
(3BNQgG (B:s
(3jYfi Hg GdTQW hjchf GdeQGO Hg Ef Sgd Gddg JYGdi Pdc hdWa di ajg Medg eG jLH Cf jMUd ai gPG GdHGH hEPG bO CKHJfG YdG Pdc aQZfG efg hfNJe Hg GdcJGH s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJhMjO hGdedd hGdfMds